2019
DOI: 10.22270/jddt.v9i1.2199
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive potential analysis of brown seaweed Sargassum wightii using UV-VIS and FT-IR

Abstract: The current study was investigated to explore the biogenic molecules of Sargassum wightii collected from the south east of Tamil Nadu, India. The biogenic molecules extracted from Sargassum wightii by using methanol as a solvent and the analysis was carried out by using UV-Visible spectroscopy and FT-IR. The UV-Visible spectrum of the methanolic extract of Sargassum wightii exposed the existence of the biogenic molecules separated from 200 -1100 nm among the absorption. The incidence of peaks from 234-676 nm d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The UV-visible and the FT-IR spectrophotometric analyses also yielded the typical signals of phenolic compounds, thus confirming their presence also in the E. intestinalis extracts [ 26 ]. The results of our study are in the line with the findings from a previous study in Padina pavonica [ 27 ] and Sargassum wightii seaweed extracts [ 28 ]. A quantitative analysis revealed that the highest content of phenols and flavonoids was present in the EEEI (about 60 and 625 mg of GAE and RUE per gram of extract for TPC and TFC, respectively), closely followed by the MEEI (about 23 and 416 mg of GAE and RUE per gram of extract for TPC and TFC, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…The UV-visible and the FT-IR spectrophotometric analyses also yielded the typical signals of phenolic compounds, thus confirming their presence also in the E. intestinalis extracts [ 26 ]. The results of our study are in the line with the findings from a previous study in Padina pavonica [ 27 ] and Sargassum wightii seaweed extracts [ 28 ]. A quantitative analysis revealed that the highest content of phenols and flavonoids was present in the EEEI (about 60 and 625 mg of GAE and RUE per gram of extract for TPC and TFC, respectively), closely followed by the MEEI (about 23 and 416 mg of GAE and RUE per gram of extract for TPC and TFC, respectively).…”
Section: Discussionsupporting
confidence: 93%
“… 29 . Peaks at 264 nm, 348 and 392 nm can be contributed to the presence of phenolics as well as flavonoids and their derivatives 30 . Data demonstrated absorption bands lies between 260 and 400 nm, which distinguish the presence of aromatic and poly-aromatic compounds comprising proteins and amino acids 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids and their derivatives have unique absorption spectra. The spectral bands of flavonoids are typically absorption spectra with maximal values in the range of 300–360 nm [ 80 ]. The absorption maximum bands for anthocyanins are at 460–560 nm, while flavones and flavonols are around 310–370 nm, as seen in peaks (350, 375, 399, 461,485, 547, and 559 nm) [ 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%